2018
DOI: 10.1590/0103-8478cr20170283
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characteristics on calves’ sale price on the western border of the state of Rio Grande do Sul, Brazil

Abstract: The demand for beef cattle with specific traits is evident from sales in auctions. While purchasing, buyers consider individual traits (e.g., muscularity, frame, racial composition, and weight) as predictors of quality, and adjust their bids according to their preferences. The present study aimed to evaluate the effect of phenotypic and racial characteristics in determining the final sale price of calves of beef cattle in official auctions at the western border of the state of Rio Grande do Sul, Brazil. Five-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Troxel and Barham (2012) argued that the genetic group affects the selling price of beef calves in Arkansas, with Aberdeen Angus being the most valued. Gonçalves et al (2018) observed higher prices paid per kg of crossbreed and European calves.…”
Section: Discussionmentioning
confidence: 89%
“…Troxel and Barham (2012) argued that the genetic group affects the selling price of beef calves in Arkansas, with Aberdeen Angus being the most valued. Gonçalves et al (2018) observed higher prices paid per kg of crossbreed and European calves.…”
Section: Discussionmentioning
confidence: 89%
“…There is a scarcity of studies on sheep farming in RS that assess trends and commercial value of male lambs according to its phenotypic characteristics, particularly with regard to the market value of the breeders and criteria used by sheep farmers to choose such animals. Conversely, bovine species have been well studied in terms of animal characteristics and related market value (Gonçalves et al, 2018).…”
Section: Introductionmentioning
confidence: 99%